Pendampingan Petani Jamur Tiram Memproduksi Asap Cair dengan Memanfaatkan Limbah Baglog - Adhiguna, Rizky Tirta; Syafi’i, Syafi’i; Putra, Rendi Wijaya; Heryanto, Abdul Roni (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The community of Payakabung village has been developing oyster mushroom cultivation since 2014. The issue in oyster mushroom cultivation is the waste from the baglogs. The purpose of this community service activity is to provide guidance to oyster mushroom farmers in utilizing waste from the baglogs to produce economically valuable products and add value through the production of liquid smoke. The community service activity uses a mentoring method for oyster mushroom farmers carried out fully in the field with a participatory andragogical learning approach. The mentoring activities consist of field surveys, problem identification, needs analysis, target group determination, program development, formulation and measurement of success indicators, mentoring strategies for the target groups, as well as monitoring and evaluation. The conclusion drawn from the activity is that the oyster mushroom farmers' group in Payakabung village is capable of independently producing 20 liters of liquid smoke from every 100 kg of waste from baglogs generated from oyster mushroom cultivation. The farmers' group has gained increased abilities, insights, and skills in developing their business through the enhancement of the substrate bag waste value through liquid smoke products